Acute effects of TCDD administration: special emphasis on testicular and sperm mitochondrial function - Mota, Paula C. (2012)
Objective: The goal of this study was to verify if 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) could have any effect on male germ cells mitochondria and in this way add new insights in how male reproductive alterations observed in other studies occur. Methods: In vivo and in vitro approaches using rat testis and human sperm as models were employed to evaluate TCDD effects on testicular and sperm mitochondria after 24 h of exposure. Results: Testicular mitochondria from TCDD-treated rats presented no differences in the bioenergetic parameters monitored except for a significantly higher electric membrane potential in the presence of ADP, corroborated when TCDD was directly added to testicular mitochondria from untreated rats. Nevertheless, sperm mitochondrial membrane potential, motility, viability, capacitation and acrosomal integrity did not change after TCDD treatment. Moreover, only few sperm cells exposed to TCDD increased their intracellular Ca2+ concentration. Conlusions: TCDD can interact directly with rat testicular mitochondria inducing small changes. This effect, however, does not seem to occur in human sperm or it may be insufficient to induce significant alterations as observed by the maintenance of sperm function. 1.